ANALISIS PENANGGULANGAN LAJU KOROSI DALAM PENERAPAN PLANNED MAINTENANCE SYSTEM (PMS) DI KAPAL KM. BUKIT RAYA - Muhammad Guntur Pratama; i Kadek Laju; Rizal Rochmansyah; Nelfi Erlinda; Rosnani (STKIP Subang, 2026)
Ship seaworthiness is a vital aspect of shipping safety that relies heavily on the integrity of the ship's structure, where corrosion poses a primary threat. To mitigate this risk, the Planned Maintenance System (PMS) is implemented as a planned maintenance standard in accordance with the ISM Code and international regulations. This study aims to analyze the mitigation of the corrosion rate in the implementation of the Planned Maintenance System (PMS) on MV. Bukit Raya to ensure ship seaworthiness. Using descriptive qualitative methods and Gap Analysis, data were collected through observation, interviews, and documentation. The results indicate that the implementation of PMS is not yet optimal due to tight operational schedules and short port stays, leading to improvisational maintenance. Non-compliance with surface preparation standards (ISO 8501-1) was found, often prioritized for aesthetic targets. This results in coating failures (blistering) and recurring corrosion, necessitating stricter supervision of technical maintenance standards.